Monitoring chemotherapy‐induced alopecia with trichoscopy. (11th July 2018) - Rossi, Alfredo; Caterina Fortuna, Maria; Caro, Gemma; Cardone, Michele; Garelli, Valentina; Grassi, Sara; Carlesimo, Marta
Summary: Background: Chemotherapy‐induced alopecia (CIA) ranks among the psychologically most devastating effects of cancer treatment for oncological patients, with an overall incidence of 65%. Nowadays trichoscopy is largely employed in the diagnosis of alopecia, but no description of CIA trichoscopic pattern is present in literature. Aims: We want to create an organic description of CIA trichoscopic aspects. Methods: Oncological patients candidate to chemotherapy drugs, afferent to our trichological outpatient were studied. Anamnesis, clinical exam, clinical global photography, pull test, trichogram, and trichoscopy were conducted at the different moments of therapeutic treatment. Results: A definite trichoscopic pattern in the different phases of treatment was observed. After the first 3 weeks of chemotherapy rare and scattered black dots, broken hairs, flame hairs and pohl pinkus appeared. At the end of chemotherapy besides the features described above, numerous thin hair in regrowth were detected, together to rare terminal hair, scattered black dots and circle hair. Three months after chemotherapy a progressive increase of follicular units and elongation of the existing hair were visible. Conclusions: We propose an description of CIA trichoscopic pattern and its evolution during the different phases of chemotherapy.